Real Life Practices and Perceptions of the Semester System: An Empirical Research - Jora, Man Bahadur (AMC Journal (Dhangadhi), 2026)
The focus of this research is on the practical application of the undergraduate semester system, which includes the delivery of syllabuses, examinations and extracurricular activities. By utilizing interview guidelines and thematic analysis of qualitative data from five faculties, the research investigates teacher practices, classroom activities, and perceptions of effectiveness. According to the findings, there is a discrepancy between student expectations and teacher practices, with teachers tending to use lecture-based techniques over more text-heavy approaches, while students prefer focused learning and easier access. Additionally, limited resources, library support and cheap devices impede self-learning through practical learning. There is a debate among faculty about the system’s overall effectiveness, particularly for general programs, although technical courses are more suitable with semester schedules. Inadequate policies and implementation, such as unclear curricula, poor planning and miscommunication of language also undermine the execution. The semester system can enhance time-bound research and autonomy, but accomplishment requires robust resources, streamlined policies to support student success, enhanced faculty education, and a more focused educational approach. However, the optimal approach to improving semester-based higher education requires adjustments to resource allocation, curricular design, and institutional planning.